2013
DOI: 10.1158/1078-0432.ccr-12-3327
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Bicalutamide in Patients with Androgen Receptor–Positive, Estrogen Receptor–Negative Metastatic Breast Cancer

Abstract: Purpose Patients with hormone receptor–negative breast cancer generally do not benefit from endocrine-targeted therapies. However, a subset with androgen receptor (AR) expression is predicted to respond to antiandrogen therapies. This phase II study explored bicalutamide in AR-positive, estrogen receptor (ER), and progesterone receptor (PgR)-negative metastatic breast cancer. Experimental Design Tumors from patients with ER/PgR-negative advanced breast cancer were tested centrally for AR [immunohistochemistr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
509
0
20

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(539 citation statements)
references
References 36 publications
(36 reference statements)
10
509
0
20
Order By: Relevance
“…Bicalutamide, an oral non-steroidal antiandrogen that competitively inhibits the binding of androgens with AR, has shown a proof-of-principle for the efficacy of minimally toxic androgen blockade in a select group of patients with ER/PgR-negative, AR-positive BC (Gucalp et al 2013). One case of complete response to bicalutamide was recently reported in a patient with metastatic triple-negative, AR-positive BC (Arce-Salinas et al 2016).…”
Section: Ar-targeting Therapy In Triple-negative/lar Bcmentioning
confidence: 99%
“…Bicalutamide, an oral non-steroidal antiandrogen that competitively inhibits the binding of androgens with AR, has shown a proof-of-principle for the efficacy of minimally toxic androgen blockade in a select group of patients with ER/PgR-negative, AR-positive BC (Gucalp et al 2013). One case of complete response to bicalutamide was recently reported in a patient with metastatic triple-negative, AR-positive BC (Arce-Salinas et al 2016).…”
Section: Ar-targeting Therapy In Triple-negative/lar Bcmentioning
confidence: 99%
“…44 In addition, multiple clinical trials currently underway for patients with TNBC have shown promising preliminary results with AR-targeted therapies against TNBCs with a higher percentage of AR þ cells. 45 We, therefore, propose testing for AR expression in all metastatic/recurrent TNBCs and primary TNBCs that do not completely respond to chemotherapy to help guide management decisions. …”
Section: Prognostic and Predictive Values Of Androgen Receptor In Tnbcsmentioning
confidence: 99%
“…Some studies show no prognostic value of AR in ER -and/or TNBC, whereas others report either improved or worsened outcomes for breast cancer patients with AR positive (AR + ) in ERand/or TNBC as reviewed by McNamara et al (16). However, a clinical phase II trial recently showed promising results for the anti-androgen bicalutamide in AR + /ER -/PR -metastatic 4 breast cancer, high-lighting AR as a promising predictive marker in breast cancer treatment (17). Another anti-androgen, enzalutamide, is currently being tested in an ongoing clinical trial (ClinicalTrials.gov identifier: NCT01597193).…”
Section: Introductionmentioning
confidence: 99%